Studies on metal α-isosaccharinic acid complexes - Nicholas D.M. Evans (2003)
This thesis details the experimental work carried out during a three year project commissioned by UK-Nirex. The main objective of the project was further developing the software package STAB, a programme produced at Loughborough University for predicting stability constants. It is intended that the software will be able to predict stability constants for complexes likely to be formed in a cementitious repository for intermediate and low level nuclear waste. Cellulosic materials in the waste in such repositories are likely to be degraded into potential ligands such as isosaccharinic acid. Thus, there is a need for knowledge of the complexes that they may form with radionuclides in the waste. [Continues.]